2007
DOI: 10.3168/jds.2006-267
|View full text |Cite
|
Sign up to set email alerts
|

A Probabilistic Neural Network Model for Lameness Detection

Abstract: A 4-balance system for measuring the leg-load distribution of dairy cows during milking to detect lameness was developed. Leg weights of 73 cows were successfully recorded during almost 10,000 robotic milkings over a period of 5 mo. Cows were scored weekly for locomotion, and lame cows were inspected clinically for hoof lesions. Unsuccessful measurements, caused by cows standing outside the balances, were removed from the data with a special algorithm, and the mean leg loads and number of kicks during milking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 27 publications
8
95
4
Order By: Relevance
“…Due to the reduced opportunities for handling cows in AMS, there is interest in finding automated means of detecting illness, including lameness. Walking platforms, which measure the force that cows exert when walking or standing, may be one option (e.g., Rajkondawar et al 2002;Rushen et al 2007) and could be incorporated into an AMS (Pastell et al 2007). However, AMS gather and maintain considerable data on the pattern of cows' visits to the milking unit and our results suggest that the visiting frequency (either a low frequency or a reduction from the usual number of visits) could be used as a tool for helping to identify lame cows.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the reduced opportunities for handling cows in AMS, there is interest in finding automated means of detecting illness, including lameness. Walking platforms, which measure the force that cows exert when walking or standing, may be one option (e.g., Rajkondawar et al 2002;Rushen et al 2007) and could be incorporated into an AMS (Pastell et al 2007). However, AMS gather and maintain considerable data on the pattern of cows' visits to the milking unit and our results suggest that the visiting frequency (either a low frequency or a reduction from the usual number of visits) could be used as a tool for helping to identify lame cows.…”
Section: Discussionmentioning
confidence: 99%
“…When performed by trained veterinarians, visual locomotion scoring performed better than Stepmetrix in detecting cows with painful lesions. Pastell and Kujala (2007) used load cells in a robotic milker with 37 cow scores to measure leg load during milking and classified 96.2% correctly as mobility score (0,1,2) against lame (mobility score 3 or above). When a cow's mobility PLF dairy score increases the cows back arches and Viazzi et al (2013) compared two imaging methods to measure the degree of arching.…”
Section: Mobility and Lameness Measurementmentioning
confidence: 99%
“…We have generally found that derived measures (stride overlap, time in triple support and speed) are more useful in detecting differences than basic kinematic measures like stride duration . Pastell and Kujala (2007) validated measures of force from cows standing in a robotic milker, modelling the data into a probabilistic neural network, against hoof lesions and gait scores, and found they could positively detect 100% lame cows with this technology. We suspect that sophisticated methods of data handling and analysing, like those reported by Pastell and Kujala (2007), will allow for better integration of objective data, and more powerful predictive models for detecting cows with hoof and leg pathologies.…”
Section: Validity Of Objective Measuresmentioning
confidence: 99%